Wege und Irrwege der politischen Geographie und Geopolitik - Schöller, Peter (ERDKUNDE, 1957)
In a first brief section the development of political geography and geopolitics in Germany since Ratzel and Kjellén is sketched and the difference between the two fields outlined; i. e. scholarly research versus practical propagandistic application, tendentiousness and forecasts. A further characteristic of geopolitics is seen in the fact that it brings the physical background, which always acts only indirectly and by the way of intermediaries, in direct relationship to the state and political life; that it thus overvalues the role of physical nature in that respect and tries to establish laws. The experience of the last decades when German geopolitics had become a passive tool rather than an active driving force in the service of Hitlerite politics and a belated imperialism, have taught us to pay closer and more critical attention to the boundary between science and pseudo-science and to the soundness of the methods employed. A brief glance is devoted to the insignificant re-blossoming of geopolitics in Germany after the last war. The Zeitschrift für Geopolitik, which reappeared again in 1951 without having changed in attitude, no longer proclaimed a unified doctrine but contained merely a polyphony of ideas and subject matter on the themes of state and space, at times with the wellknown nationalistic tendencies there between the lines. Taking a small brochure as example, a pseudo-science is exposed which, by using vague arrows and parallelograms of forces, jumps across countries and centuries and ends in deterministic over-simplifications. During the Hitler regime genuinely scholarly political geography in Germany was condemned to silence. After the war it took at first second place behind the previously neglected development of other principles in the field of social geography, but from 1951 onward it has with new problems and in a more prominent way entered once more the field of academic discussion. In France, where the challenge of Ratal’s ideas was taken up early, political geography developed in the direction of a géographie humaine, where the onesidedness of Ratzel’s work, with its emphasis on the natural environment was corrected by giving due weight to the social factors. The central concern of its work came to be the investigation of social groups of the same way of life. The economic geography of the Soviet Union replaced the onesidedness of geographical determinism by the other onesidedness that only the type of production and its reflexes on society are decisive for the state and politics, according to the laws of social economics as developed by Marx. In the example of the book by Sernjonov which is directed in particular against the Fascistic American Geopolitics, the Soviet propaganda purpose aimed against the strongest adversary, strongest as regards military forces as well as political power, emerges clearly in the polemical excesses. The geopolitical attempts in England and America are largely based on Mackinder’s publications. The doctrines of German geopolitics found a more pronounced echo in the U.S.A. only as late as the war years 1941—45. It is significant to note that it was equally characteristic of American as of German geopolitics that it always adjusted itself in a most flexible way to every change of the world situation. In contrast to this development which had led into military strategy and pseudo-science and which merely meant reinforcement and encouragement for Karl Haushofer and his circle, scientific political geography was able to hold its own. As an example of an aberration, the pretentious work by Goblet is analysed. There an environmentalism, at times even extreme determinism, is combined with lack of clear thought, untenable generalizations, and expressions of sentiments out of place in what claims to be a work of scholarship. By denying the relevance of all forces which are active in a nation, e. g. national heritage, language and civilization, by advocating the fixing of state boundaries on the principle of power politics and advocating the re-settling of ethnical minorities, dangerous geopolitical consequences arise. The future course of political geography is finally seen, following Hassinger’s suggestion, in a reversal of the direction of the inquiry. It is no longer the aim first of all to interpret the state and political action on the basis of its geographical conditions, but rather to grasp the politicalgeographical forces which act upon the cultural landscape and to investigate their landscape shaping and functional consequences. Thus a General Political Geographie will have a truly geographical aim: to contribute by its investigations to social geography and the study of the cultural landscape. Towards that goal important preliminary contributions will arise in addition to the justified and necessary worldwide comparative observation and interpretation of the political-geographical scene, particularly from methodologically intensified studies of regional problems. On the example of recent publications some of the particular tasks of research are characterized. Particular emphasis is accorded to the problems connected with political boundaries, whose effects stand in an indivisible interrelationship with the personality and distinctiveness of countries, to the tracing of the after-effects of former colonial rule and the birth of new states, to the regional-administrative divisions within a state and the capital-city question. The ultimate aim of regional political geography must be to contribute towards regional geography through the appreciation of the characteristic political features of states and politically determined zones of the earth.